Experimental induction of hypothyroidism and goitre in goat kids: Clinical, pathological and histomorphometric findings - Colque Caro, Luis Adrián; Barbeito, Claudio Gustavo; Moore, Prando Dadin; Micheloud, Juan Francisco (Elsevier, 2025)
The study of hypothyroidism and experimentally induced goitre in young goats enables the characterization of hormonal dynamics and histological alterations in the thyroid gland. The objective of this study was to characterize histopathological and histomorphometric changes in the thyroid glands (TG) of goat kids following experimental induction of goitre using 6-n-propyl-2-thiouracil (PTU). Eighteen healthy lactating Saanen goat kids (35 days old; 6.2 kg body weight) were randomly assigned to three groups: control (basal diet +3 ml fresh milk), low-dose PTU (3.5 mg/kg BW/day in 3 ml milk), and high-dose PTU (7 mg/kg BW/day in 3 ml milk). The study spanned 116 days, during which participants underwent weekly body weight monitoring and PTU dose adjustments. At the conclusion of the trial, necropsies were conducted on 16 animals, and their TGs were evaluated both macroscopically and microscopically. Blood samples were collected on a biweekly basis to assess circulating thyroid hormone levels. No significant differences in weight gain were observed during the first 56 days; however, from day 56 onward, children in the high-dose PTU group exhibited reduced average daily gain compared to the low-dose and control groups. Thyroid gland weights exhibited an increase in both treated groups (up to 10.5 μg), accounting for 0.04 % and 0.03 % of body weight in the low- and high-dose groups, respectively, compared to 0.01 % in the control group. A histopathological evaluation revealed marked follicular hyperplasia and hypertrophy, with significant alterations in follicular morphology, epithelial height, and interfollicular spacing. Hormonal profiles revealed dose-dependent disruptions in T3, T4, and T3/T4 ratios, with the most pronounced alterations observed in high-dose PTU-treated animals. Chronic administration of PTU (propylthiouracil) led to significant structural and functional alterations in the thyroid gland, validating the experimental model's suitability for investigating iodine deficiency–related goitre in young ruminants.